Stress field based truss model for shear-critical prestressed concrete beams. (August 2015) - De Wilder, K.; Lava, P.; Debruyne, D.; Wang, Y.; De Roeck, G.; Vandewalle, L.
Abstract: Despite more than a century of continuous effort, shear still remains one of the few areas of research into fundamentals of the behavior of concrete structures where dispute remains amongst researchers about the mechanisms that enable the force flow through a concrete member and across cracks. This paper firstly presents the results of 9 full-scale prestressed concrete I-shaped beams subjected to a four-point bending test until failure. Two stereo-vision digital image correlation (DIC) systems were used to discretely measure three-dimensional displacements in both zones where a shear force exists. A numerical technique has been adopted to generate optimized patterns for DIC and the resulting speckle pattern was applied onto each specimen using a stencil printing technique. Using the sectional shear design procedure from Eurocode 2, a severe underestimation of the experimentally observed shear capacity was found. Therefore, a parametric nonlinear finite element (FE) model was constructed to further investigate the mechanical behavior. The ability of the FE model to reconstruct the observed structural behavior was validated using the experimental data concerning failure load, failure mode and (full-field) displacement data. Finally, based on the numerically obtained stress fields, an internally statically indeterminate truss model was proposed which clearly visualizes the flow of forces and accurately describes the observed failure load and failure mode. A simple relationship between the applied shear force and the amount of shear force carried by the shear reinforcement was proposed. The proposed relationship was validated using the reported experimental data.